Deep sternal wound infection following cardiac surgery: A comparison of the monolateral with the bilateral pectoralis major flaps. Issue 3 (17th February 2020) - Lo Torto, Federico; Turriziani, Gianmarco; Donato, Casella; Marcasciano, Marco; Redi, Ugo; Greco, Manfredi; Miraldi, Fabio; Ribuffo, Diego
Abstract: Deep sternal wound infections are a serious complication following sternotomy for cardiothoracic surgery. "Conventional" treatment provides debridement and secondary closure or closed catheter irrigation. The combination of the Negative Pressure Therapy with flap coverages is an accepted technique and one or both Pectoralis Major muscles could be chosen. A multistep protocol was adopted. One hundred and sixty seven patients were treated with the combination of Negative Pressure Therapy with the Pectoralis Major muscle flap: 86 monolateral flap and 81 bilateral flap reconstruction. The main complications (hematoma, seroma, dehiscence, and re‐infection), the need for re‐intervention, mortality rates, Intensive Care Unit, and hospitalisation time were assessed. The mono‐pectoralis group had fewer complications and need for revision, with a shorter hospital stay. A statistically significant difference emerged for the hematoma rate ( P = .0079). Monolateral flap should to be preferred because with the same coverage effectiveness, it guarantees the saving of controlateral muscle with its functionality and the possibility of its use in case of failure. Furthermore, as the technique is less invasive, it can be reserved for more fragile patients.